MAGNESIUM DEFICIENCY OF PATIENTS WITH HORMONE DEPENDENT DISEASES: PHARMACOEPIDEMIOLOGICAL PROFILE AND LIFE QUALITY ASSESSMENT - Dmitry Vladislavovich Blinov; Juliana Vladimirovna Zimovina; Elena Anatol'evna Sandakova; Tat'yana Igorevna Ushakova (Фармакоэкономика)
Magnesium deficiency (MD) as a condition connected with wide spectrum of obstetric pathology is more studied and known than in gynecology. Prevalence of MD in patients with gynecological diseases is unknown. The most interesting is connection with hormonal dependent conditions because magnesium plays important role in hormonal metabolism.Objective. Describe the profile of outpatient women in hormone dependent conditions with MD and evaluate the effectiveness of therapy against MD including quality of life (QoL).Materials and methods. Study was performed in 21 cities of 7 Russian regions. The disease part included outpatient women in hormone dependent conditions and the product part included outpatient women in hormone dependent conditions with magnesium deficiency and receiving fixed dose combination of magnesium citrate and pyridoxine. For diagnostic of MD doctors used MD questionnaires and magnesium blood level. For estimation of efficacy of the therapy additionally 10-point scale of changes in the MD symptoms severity as well as quality of life questionnaire the World Health Organization WHOQOL-BREF after 4 weeks therapy were used.Study results. A total of 9.168 women were enrolled. The disease part included 9.168 women and the product part – 2.101 women. Prevalence of MD in group of patients taken hormonal contraceptives was 67.3%; in women with premenstrual syndrome – 73.8%; in patients with climacteric syndrome without menopausal hormonal therapy (MHT) – 72.3%; in patient with climacteric syndrome taken MHT – 79.4%; in patients with osteoporosis – 82.1%; in women with other hormone depended conditions – 76.2%. Effectiveness of the therapy was estimated as full well and well in 89.4%, tolerability – in 92.4% patients. QoL was statistically improved. The survey results indicate that after 4 weeks of the therapy the satisfaction of patients with their physical and well-being significantly increased from 21.1±4.5 to 26.2±3.5 points (p<0.001), psychological increased from 18.2±3.7 to 22.2±3.6 points (p<0.001), assessment of social relations improved from 24.8±4.9 to 28.1±4.4 points (p<0.001), satisfaction with the environment increased from 9.3±2.7% 11.0±2.8 (p<0.001).Conclusion. High prevalence of MD was revealed in women with hormone depended conditions. Appointment of fixed dose combination of magnesium citrate and pyridoxine reduces MD, effectively eliminates the major symptoms, subjectively and objectively improves the condition of patients, as well as a positive effect on QoL.